2022
DOI: 10.1111/jam.15730
|View full text |Cite
|
Sign up to set email alerts
|

Complete-genome sequence and in vitro probiotic characteristics analysis of Bifidobacterium pseudolongum YY-26

Abstract: Aims The aim was to isolate a neotype bifidobacteria strain and evaluate its in vitro probiotic potential. Methods and Results Bifidobacterium pseudolongum YY‐26 (CGMCC 24310) was isolated from faeces of mice treated with low‐molecular‐weight hydrolyzed guar gum (GMPS) and identified based on 16S rRNA sequence and genome sequence. Whole‐genome sequencing obtained using PacBio's single‐molecular and Illumina's paired‐end sequencing technology. A genome of 2.1 Mb in length, with 1877 predicted protein‐coding seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…lactis BB-12.It was illustrated by Yu et al that the scavenging activities of B . pseudolongum YY-26 on DPPH radical and superoxide anion radical were 97.58% and 43.13%, respectively [ 68 ]. Kang et al [ 69 ] also confirmed that B .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lactis BB-12.It was illustrated by Yu et al that the scavenging activities of B . pseudolongum YY-26 on DPPH radical and superoxide anion radical were 97.58% and 43.13%, respectively [ 68 ]. Kang et al [ 69 ] also confirmed that B .…”
Section: Discussionmentioning
confidence: 99%
“…longum BL-10 isolated from healthy baby feces by Dong et al [67], exhibited better antioxidant performance than B. animalissubsp. lactis BB-12.It was illustrated by Yu et al that the scavenging activities of B. pseudolongum YY-26 on DPPH radical and superoxide anion radical were 97.58% and 43.13%, respectively [68]. Kang et al [69] also confirmed that B. bifidum MG731 showed the highest DPPH radical scavenging activity (90.6%), and B. lactis MG741 displayed the highest ABTS radical scavenging activity (99.5%).…”
Section: Plos Onementioning
confidence: 92%